2019
DOI: 10.1038/s41598-018-36504-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends and inequalities in coronary angiography utilization in the management of non-ST-Elevation acute coronary syndromes in the U.S.

Abstract: Coronary angiography (CA) is the basis of an invasive management strategy in non-ST elevation acute coronary syndromes (NSTEACS). There are limited contemporary data on national temporal trends in utilization of CA in different patient subgroups. We sought to investigate temporal trends, predictors and clinical outcomes associated with the use of CA in the US. Using the Nationwide Inpatient Sample (NIS) from 2004–2014, we identified all inpatient admissions, age ≥18, with a primary diagnosis of NSTEACS. Descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…Data from the National Inpatient Sample database in the USA showed that coronary angiography was done in 78% of patients with NSTEMI aged 60 years or younger, compared with 38% of patients aged 81 years or older. 5 In our study, 49% of eligible patients underwent invasive management during their index admission. These differences do not necessarily reflect ageism, rather they reflect insufficient data to guide clinical practice.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Data from the National Inpatient Sample database in the USA showed that coronary angiography was done in 78% of patients with NSTEMI aged 60 years or younger, compared with 38% of patients aged 81 years or older. 5 In our study, 49% of eligible patients underwent invasive management during their index admission. These differences do not necessarily reflect ageism, rather they reflect insufficient data to guide clinical practice.…”
Section: Discussionmentioning
confidence: 90%
“… 10 , 11 Studies of temporal trends using registry data from the USA and Europe suggest that over the past 15 years the progressive switch from a non-invasive to more invasive approach in older patients with NSTEMI has been accompanied by declining mortality. 5 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among older adults with acute myocardial infarction (AMI), there has been an increasing use of invasive coronary angiography and coronary revascularization in the United States, 1 Canada, 2 and Europe 3 over recent decades. For example, in the United States, the use of invasive coronary angiography for non-ST-elevation acute coronary syndromes increased from 49.7% in 2004 to 66.0% in 2014 among patients aged 71 to 80 years and from 27.2% to 37.9% among patients >80 years.…”
mentioning
confidence: 99%
“…For example, in the United States, the use of invasive coronary angiography for non-ST-elevation acute coronary syndromes increased from 49.7% in 2004 to 66.0% in 2014 among patients aged 71 to 80 years and from 27.2% to 37.9% among patients >80 years. 1 While these procedures have multiple benefits, including the potential for reduced mortality and recurrent AMI, 4,5 they also confer risk. This risk increases with advancing age, as physiologic changes coupled with comorbidities increase the risk of treatment-related complications, including bleeding, acute kidney injury, vascular complications, and stroke.…”
mentioning
confidence: 99%